Competition in the South African manufacturing sector: An empirical probe - G. Djolov (South African Journal of Business Management, 2015)
This paper empirically probes competition in the South African manufacturing sector using the latest published data on the industries of this sector released by the national statistical office. It is found that enterprise behaviour in this sector is governed by competition where the negativity between industry concentration and its linkages with output, employment, labour productivity, profit margins, rates of return, investment, and producer prices, has more to do with the limiting of rivalry between enterprises, as opposed to growing concentration promoting by itself poor economic performance. The findings are consistent with earlier investigations. From a managerial perspective, they suggest that while adaptive behaviour by enterprises through imitation or experimental actions is likely to lead to positive profitability, any resultant profit margins and rates of return are ultimately dependant on how successful or decisive enterprises are at innovating if they wish to grow their output, raise labour productivity, invest and employ more, as well as secure the demand-inducing prices commensurate with their innovative record. Thus the success of an enterprise rests on its ability to innovate.
Keywords: 650